Genotranscriptomic meta‐analysis of the CHD family chromatin remodelers in human cancers – initial evidence of an oncogenic role for CHD7. Issue 10 (21st July 2017) - Chu, Xiaofang; Guo, Xuhui; Jiang, Yuanyuan; Yu, Huimei; Liu, Lanxin; Shan, Wenqi; Yang, Zeng‐Quan
Abstract : Chromodomain helicase DNA binding proteins (CHDs) are characterized by N‐terminal tandem chromodomains and a central adenosine triphosphate‐dependent helicase domain. CHDs govern the cellular machinery's access to DNA, thereby playing critical roles in various cellular processes including transcription, proliferation, and DNA damage repair. Accumulating evidence demonstrates that mutation and dysregulation of CHDs are implicated in the pathogenesis of developmental disorders and cancer. However, we know little about genomic and transcriptomic alterations and the clinical significance of most CHDs in human cancer. We used TCGA and METABRIC datasets to perform integrated genomic and transcriptomic analyses of nine CHD genes in more than 10 000 primary cancer specimens from 32 tumor types, focusing on breast cancers. We identified associations among recurrent copy number alteration, gene expression, clinicopathological features, and patient survival. We found that CHD7 was the most commonly gained/amplified and mutated, whereas CHD3 was the most deleted across the majority of tumor types, including breast cancer. Overexpression of CHD7 was more prevalent in aggressive subtypes of breast cancer and was significantly correlated with high tumor grade and poor prognosis. CHD7 is required to maintain open, accessible chromatin, thus providing fine‐tuning of transcriptional regulation of certain classes of genes. We found that CHD7 expression was positively correlated with a small subset of classical oncogenes, notably NRAS, in breast cancer. Knockdown of CHD7 inhibits cell proliferation and decreases gene expression of several CHD7 targets, including NRAS, in breast cancer cell lines. Thus, our results demonstrate the oncogenic potential of CHD7 and its association with poor prognostic parameters in human cancer. Abstract : Chromatin remodelers are key players in the regulation of chromatin accessibility and gene transcription. Here, we report that among nine CHD chromatin remodelers, CHD7 exhibited the highest frequency of genetic amplification/mutation, and was overexpressed in a spectrum of human tumors. CHD7 overexpression was significantly associated with a low survival rate and aggressiveness in breast cancer. CHD7 likely regulates a set of cancer genes including NRAS; and CHD7 knockdown inhibits growth of aggressive basal‐like breast cancer.